Study on Enhanced Oil Recovery Technology of LH2500 New Salt-Resistant Polymer - Wang Weian (E3S Web of Conferences, 2022)
In order to explore a new way to improve the development efficiency of polymer flooding in sewage system, the laboratory evaluation of LH2500 new salt-resistant polymer was carried out, and the field test was carried out in the middle of Xing 6 area in Daqing Oilfield. The indoor results show that compared with the 25 million polymer of Daqing Refining & Chemical Co., Ltd. under the same concentration of the cleaning system, the viscosity of LH2500 salt-resistant polymer is about 29% higher, the residual resistance is more than 10%, and the dynamic adsorption capacity is more than 5%. Increase the recovery rate by 4 percentage points. In the field application process, through optimizing the design of the oil displacement scheme of salt-resistant polymer and establishing the on-site dynamic tracking and adjustment technology, the development effect of the test area is remarkable, with the lowest water cut falling below 80% and the maximum drop reaching 15.6 percentage points, with the low value period as long as 22 months, the staged enhanced oil recovery rate reaching 13.5 percentage points, and the ultimate enhanced oil recovery rate is expected to reach more than 16 percentage points. Compared with ordinary polymer blocks, the recovery ratio in the test area is increased by more than 4 percentage points. At the same time, due to the dilution of sewage system, the excess sewage in oil field is effectively alleviated, and the high and stable yield of environmental protection is realized.